2002
DOI: 10.1023/a:1014681314034
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Radionuclide angiography (RNA) permits analysis of contractility and conduction abnormalities. We determined the parameters of normal ventricular synchronization, assessed the reproducibility of the technique, and compared first harmonic (1H) and third harmonic (3H) analysis. Forty-four normal subjects (28 men and 16 women) were studied. RNA was performed in left anterior oblique (LAO) and left lateral (LL) projections. The onset (To), mean time (Tm), total contraction time (Tt) for right ventricle (RV) and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Various studies have assessed the feasibility of ERNA in assessing mechanical synchrony and have also validated the accuracy of the method. [19202122] However, to make this technique proceed from the bench to the bedside, we compared and correlated ERNA with the modality, the cardiologist is most familiar with, that is, the echocardiography. To the best of our knowledge, this is the first study comparing ERNA and STE for the assessment of LV mechanical dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have assessed the feasibility of ERNA in assessing mechanical synchrony and have also validated the accuracy of the method. [19202122] However, to make this technique proceed from the bench to the bedside, we compared and correlated ERNA with the modality, the cardiologist is most familiar with, that is, the echocardiography. To the best of our knowledge, this is the first study comparing ERNA and STE for the assessment of LV mechanical dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Using phase analysis, ERNA has also been investigated for the assessment of dyssynchronous cardiac contraction, and it is proven to be highly reproducible. [18192021] Being noninvasive, highly reproducible, and relatively easy to perform, it may be one of the most promising techniques to quantify dyssynchrony.…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation of the pixels' phase angles measured in each ventricular Region of Interest (ROI) represents intraventricular dyssynchrony and the difference between the means of the phase angles of both ventricular ROI represents interventricular dyssynchrony [24]. Several studies have reported an improvement of interventricular and intraventricular dyssynchrony after CRT, using the Fourier phase analysis of ERNA images [2529].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in patients with dilated cardiomyopathy and wide QRS, Toussaint et al found that in the subgroup with LVEF of [ 15% at baseline, interventricular dyssynchrony was predictive of at least a 5% increase in LVEF at follow-up with a positive predictive value of 83%. 2 Kerwin et al also reported improvement in LVEF in patients with interventricular dyssynchrony at baseline who were implanted with BiV. 12 In another smallscale study, a threshold of 50°for interventricular contraction heterogeneity on RNA phase analysis correlated with symptoms improvement after LV pacing 13 and the decrease in the interventricular contraction delay was the most predictive parameter.…”
mentioning
confidence: 98%
“…Even if echocardiography is widely available, inexpensive and non-radiative, RNA is more reproducible, notably to quantify ventricular synchronization. 2 In contrast to echocardiography, RNA is not operator-dependent, relying on automated contour delineation to determine ventricular volumes, and Fourier phase analysis to provide contraction delays. RNA is also less limited than echocardiography by patients' morphology, specifically in female and obese patients.…”
mentioning
confidence: 99%